The Mechanism of Allosteric Inhibition of Protein Tyrosine Phosphatase 1B - Li, Shuai; Zhang, Jingmiao; Lu, Shaoyong; Huang, Wenkang; Geng, Lv; Shen, Qiancheng; Zhang, Jian (PLOS ONE, 2014)
As the prototypical member of the PTP family, protein tyrosine phosphatase 1B (PTP1B) is an attractive target for therapeutic interventions in type 2 diabetes. The extremely conserved catalytic site of PTP1B renders the design of selective PTP1B inhibitors intractable. Although discovered allosteric inhibitors containing a benzofuran sulfonamide scaffold offer fascinating opportunities to overcome selectivity issues, the allosteric inhibitory mechanism of PTP1B has remained elusive. Here, molecular dynamics (MD) simulations, coupled with a dynamic weighted community analysis, were performed to unveil the potential allosteric signal propagation pathway from the allosteric site to the catalytic site in PTP1B. This result revealed that the allosteric inhibitor compound-3 induces a conformational rearrangement in helix α7, disrupting the triangular interaction among helix α7, helix α3, and loop11. Helix α7 then produces a force, pulling helix α3 outward, and promotes Ser190 to interact with Tyr176. As a result, the deviation of Tyr176 abrogates the hydrophobic interactions with Trp179 and leads to the downward movement of the WPD loop, which forms an H-bond between Asp181 and Glu115. The formation of this H-bond constrains the WPD loop to its open conformation and thus inactivates PTP1B. The discovery of this allosteric mechanism provides an overall view of the regulation of PTP1B, which is an important insight for the design of potent allosteric PTP1B inhibitors.